LH level on the antagonist administration day as a predictor of the reproductive outcomes in women with normal ovarian function - Pang, Conghui; Wang, Kehua; Wang, Ruihan; Guo, Danyang; Wen, Zixi (Frontiers in Endocrinology, 2023)
Introduction The addition of antagonists is mainly based on estrogen level and follicle size, while LH level has not received sufficient attention.In this study, LH Level on the antagonist administration day was used as the main research objective to explore its relationship with laboratory indicators and pregnancy outcomes. Methods and Analysis We enrolled 854 patients with normal ovarian function undergoing in-vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) between May 2021 to May 2022 at the Reproductive Center of Shandong University of Traditional Chinese Medicine.We used the quartile method to group LH levels on the antagonist administration day. There were four groups: Q1 (0.53IU/L≤LH ≤ 1.89IU/L); Q2 (1.89IU/L<LH ≤ 3.01IU/L); Q3 (3.01IU/L<LH≤ 5.29 IU/L); Q4 (5.29IU/L<LH ≤ 8.72IU/L). A total of 452 fresh embryo transplantation cycles and 1726 Frozen embryo transplantation cycles were carried out. Result There were significant differences among the four groups in terms of total Gn dosage, E2, P and LH on trigger day, number of retrieved oocytes, number of 2PN embryos, number of blastocysts, Number of ET and fresh ETR.There is a significant correlation between LH on antagonist administration day and Basal LH Level,LH on trigger day,number of oocytes retrieved,number of 2PN embryos,number of blastocysts, number of ET.Using Fresh ETR,Fresh CPR,OHSS and Cumulative CPR as the criterion respectively, the optimal cut-off value for evaluating LH on antagonist administration day was 4.18IU/L,3.99IU/L,4.63IU/L,4.66IU/L. Conclusion There was a significant positive correlation between LH on the antagonist administration day and number of oocytes retrieved,number of 2PN embryos,number of blastocysts.LH on the antagonist administration day could predict Fresh CPR,OHSS and Cumulative CPR to some extent.